PEMANFAATAN LAHAN PEKARANGAN MELALUI BUDIDAYA HIDROPONIK DAN BUDIKDAMBER DI DESA GANDANG BARAT KECAMATAN MALIKU KABUPATEN PULANG PISAU - Siti Zubaidah -; Elsa Yosepha; Yunika Irawati; Ody Sinatra; Julianti Agung Wati; Eflin Mahdina; Roslina Simanullang; Yulianti Murib; Achmad Faried Rindhianto; Benni Randy Sitanggang; Wahyu Mandala Putra; Davidcol Julians Lonto; Lidya Pranata Wardany; Felinsia Savera; Ray Aldo Sahatma Sinurat; Riccad Suhastra Girsang (LPPM Universitas Palangka Raya, 2022)
The yard of the house is an area around the house which is limited by the size according to its legalization. In Gandang Barat Village, the yard is generally underutilized. The yard of the house is expected to be able to meet the needs of vegetables at the household level so that household expenses can be suppressed. Therefore, it is necessary to use the yard for the cultivation of vegetables and fish, among others, through hydroponic technology and budikdamber. Hydroponics is the cultivation of vegetables without using soil where nutrients are given to plants through water media, while budikdamber is the cultivation of vegetables in buckets that are integrated with fish. Various kinds of vegetables that can be cultivated through hydroponics and budikdamber include lettuce, kale, and pakcoy. These foodstuffs contain lots of antioxidants and are in great demand by the public, both the lower middle class and the upper middle class. However, the people of Gandang Barat Village still do not know the techniques of hydroponic cultivation and budikdamber. Seeing this problem, the KKN students of the Gandang Barat Village group tried as much as possible to provide knowledge to the community about how to use their yards to make it more useful through hydroponic vegetable cultivation and bucket fish cultivation (Budikdamber).